Analyzing the Analytical Thinking Skills included in The Content Of the Science Book For The Fourth Grade Basic in the Syrian Arab Republic (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aims to define the analytical thinking skills included in the science book for the fourth basic grade, and to achieve this goal a list of the analytical thinking skills to be included in the content of this book has been prepared, and the list consisted of (16) main skills.The results of the research showed that the science textbook for the fourth basic grade has included the content of the science book for the fourth basic grade a number of analytical thinking skills in varying proportions from one skill to another, especially the skills of generalization, forecasting and observation procedure that got high percentages compared to the skills of series work, seeing relationships, identifying traits and arranging And setting priorities, the distinction between similar and different that included in the content by small percentages, did not include the content of the science textbook for the fourth grade A number of analytical thinking skills are: the skill of defining properties, interviewing, building the standard, and finding patterns, as they did not get any repetition in the content of the student bookBased on the results of the research, it was suggested to include all the analytical thinking skills mentioned in the national standards in the content of the science textbook for the fourth grade, according to a clear and specific strategy.